Survival of the Fittest: A Review on Charles Dickens’ ‘Oliver Twist’ - Reddy, PR Chandra Reddy (Integrated Journal for Research in Arts and Humanities, 2024)
The story of Oliver Twist follows Oliver from his birth in a workhouse in England, uncovering the contemporary systems that lead him to Mr. Brownlow and Mrs. Maylie at last. It takes a sharp turn taking Oliver back to Mr. Brownlow as an adopted son. Dickens gives the boy a full circle of reason from the birth of uncertainty to life of certainty by making good win over evil, of course with the sacrifice of Nancy. With the characters like Charley Bates, Jack Dawkins, Fagin, Bill Sikes, Old Sally, Nancy, Mr. Brownlow, Mrs. Bedwin, Mrs. Maylie and many, the author reveals the systems and influences that lead them to make certain decisions that have altered Oliver’s life. When Oliver's mother dies after giving him birth, she disappears unidentified. Considering her death without a marriage ring on her finger, she is assumed to be unmarried and thus considered dishonored. As a baby boy, Oliver is seen as unworthy and is kept oppressed by the systems in place of helping him. As a child, Oliver Twist is accommodated in a children orphanage. The wording like, ‘less-than, inhuman, subhuman,’ alone reveals the way orphaned children are treated. Once he is old enough to work, at only nine years old, he is sent to a workhouse. These workhouses are meant to help the poor, but through Oliver's experiences, the readers can understand that they use the poor as bonded labour while greedily using and abusing them. Although Nancy is at first guilty in the crimes against Oliver, it is revealed that she has suffered in similar ways. She attempts to help Oliver and this sends Bill Sikes into an uncontrollable rage. Her murder reveals Bill's cruelty and draws sympathy for Nancy. Unlike her friends, Nancy tries to turn her life around, acting in kindness to save the boy. Although Oliver suffered throughout the book, his desire for to be good leads him to salvation with the honorable Mr. Brownlow. The unrestrained cruelty and corruption of Bill Sikes and Fagin led to their deaths. The author has martyred Nancy but punishes the characters that choose to continue to practice crime and violence. At the end, the good characters enjoy and the bad characters suffer.